The Neural Correlates of Spoken Sentence Comprehension in the Chinese Language: An fMRI Study - Liu H; Chen SHA (Psychology Research and Behavior Management, 2020)
Hengshuang Liu,1,2 SH Annabel Chen2– 5 1Bilingual Cognition and Development Lab, National Key Research Center for Linguistics and Applied Linguistics, Guangdong University of Foreign Studies, Guangzhou, People’s Republic of China; 2Psychology, School of Social Sciences (SSS), Nanyang Technological University, Singapore; 3Centre for Research and Development in Learning (CRADLE), Nanyang Technological University, Singapore; 4Lee Kong Chian School of Medicine (LKCMedicine), Nanyang Technological University, Singapore; 5National Institute of Education, Nanyang Technological University, SingaporeCorrespondence: SH Annabel Chen Email annabelchen@ntu.edu.sgPurpose: Everyday social communication emphasizes speech comprehension. To date, most neurobiological models regarding auditory semantic processing are based on alphabetic languages, where the character-based languages such as Chinese are largely underrepresented. Thus, the current study attempted to investigate the neural network of speech comprehension specifically for the Chinese language.Methods: Twenty-two native Mandarin Chinese speakers were imaged while performing a passive listening task of forward and backward sentences. Sentences were used as task stimuli, as sentences compared with words were more frequently utilized in daily speech comprehension.Results: Our results suggested that spoken Chinese sentence comprehension may involve a neural network comprising the left middle temporal gyrus, the left anterior temporal lobe, and the bilateral posterior superior temporal lobes. The occipitotemporal visual cortex was not found to be significantly involved with the sentence-level network of spoken Chinese comprehension, as bottom-up visualization process from homophones to visual forms may be less needed due to the availability of top–down contextual controls in sentence processing. In addition, no significant functional connectivity was observed, likely obscured by the low cognitive demand of the task conditions. Limitations and future directions were discussed.Conclusion: The current Chinese network seems to largely resemble the auditory semantic network for alphabetic languages but with features specific to Chinese. While the left inferior parietal lobule in the dorsal stream may have little involvement in the listening comprehension of Chinese sentences, the ventral neural stream via the temporal cortex appears to be more emphasized. The current findings deepen our understanding of how the semantic nature of spoken Chinese sentences influences the neural mechanism engaged.Keywords: Chinese, character-based languages, auditory semantic network, spoken sentences, speech comprehension